Influence of Digital Transformation on Mergers and Acquisitions Processes - Y. M. Tsygalov; M. A. Bakhareva (Управленческое консультирование)
Mergers and acquisitions are a recognized and effective mechanism for the development of companies. Depending on the goals, mergers and acquisitions (M&A) can strengthen the organization’s market position, create new competitive advantages, enter new sales markets, acquire missing competencies, radically change key business parameters and improve the company’s structure. In Russia, the theoretical and methodological foundations of mergers and acquisitions are represented quite widely. Investigated the processes of mergers and acquisitions, examined the possible negative effects reflected in the decline in the value of the combined company. The development of business processes, primarily digital transformation, has a significant impact on the effectiveness of M&A. In 2016–2019 Among the 10 largest M&A transactions, both in the world and in Russia, information technology companies are regularly included. The paper considers one of the most relevant trends in the modern world - the digital transformation of the business, as well as the dependence on technologies and digital technologies, occurring not only in the IT company, but also in the non-technology sector company. The purpose of the research is to prove the direct relationship between digital transformation and M&A. In the course of the research, the following methods were used: analysis and synthesis, comparison, assessment and generalization of research results and reports of consulting companies. It is proved that digitalization is one of the most important reasons and drivers. The main recommendations for their implementation were formulated.